Judicial Decisions and Legal Autopoiesis: Law as a Living System - Susilo, Erwin (Fakultas Syariah INSURI Ponorogo, 2025)
Law, as a living system, evolves through continuous communication, enabling it to adapt to social changes and technological advancements. This research examines the question of how law reproduces itself within the framework of judicial decision-making in Indonesia, to explain the theoretical and practical roles of judges in maintaining the vitality of the legal system. Using a normative-conceptual (doctrinal-philosophical) approach, this research combines Niklas Luhmann's autopoiesis theory, Hans Kelsen's pure law theory, Jürgen Habermas's communicative action theory, Ronald Dworkin's concept of law as integrity, and Pierre Bourdieu's theory of symbolic power to analyze how judicial decisions function as a mechanism for legal reproduction. The research results show that judges in Indonesia not only apply existing norms but also interpret and reconstruct them to align with social and technological developments. For example, this is evident in Supreme Court Decisions Number 1794 K/Pdt/2004 and Number 230/G/TF/2019/PTUN-JKT, which demonstrate how judges' legal considerations integrate normative coherence, communicative legitimacy, and social responsiveness. This research concludes that law in Indonesia functions as an autopoietic system—capable of independently reproducing itself, adapting, and sustaining itself through judicial communication, thus remaining relevant, legitimate, and responsive to the dynamics of contemporary society.